The other world: according to descriptions in medieval literature - Patch, Howard Rollin (Smith College studies in modern languages, 1950)
Frontmatter -- PREFACE -- CONTENTS -- INTRODUCTION -- I. MYTHOLOGICAL ORIGINS: ORIENTAL AND CLASSICAL -- II. AMONG THE CELTS -- III. GERMANIC MYTHOLOGY -- IV. THE LITERATURE OF VISIONS -- V. JOURNEYS TO PARADISE -- VI. ALLEGORY -- VII. THE ROMANCES -- CONCLUSION -- BIBLIOGRAPHY -- INDEX